Integrating virtual reality and electroencephalography: applications, opportunities and challenges from a patents review - Mendes, Bianca Louise C.; Ferreira, Yasmim Thasla; Almeida, Viviane; Lopes, Camila; Silva, Victoria; Lima, Sofia; Almeida, Lucas; Catapan, Márcio; Almeida Filho, Daniel; Winkler, Ingrid (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
With the increasing availability of physiological sensors and immersive technologies, the integration of electroencephalography (EEG) and virtual reality (VR) has emerged as a promising approach for developing interactive systems that respond to users’ cognitive and emotional states. To better understand the technological directions and industrial strategies shaping this field, this work presents an exploratory search that examines patent records related to the integration of EEG and VR, to identify current applications, opportunities and challenges in this emerging field. A structured search on the Derwent Innovation platform identified 376 patents with application dates between January 2018 and December 2023, analyzed according to classification codes, geographic coverage, assignee profiles, hardware and software references, and application domains. Results indicate a strong focus on medical and cognitive monitoring applications, led by filings from the United States and China, with contributions from both academic and corporate actors. However, limited technical disclosure, reproducibility issues, and persistent challenges in signal quality and validation remain. This study complements academic literature by offering a comprehensive patent-based perspective on the state of the art, highlighting gaps and opportunities for future development.